Okay... so here's the deal

It's given

S1 + S2 = 16 ---------- Eqn. (1)

And S1 X S2 = 3(S1 + S2) = 3 X 16 = 48 -------- Eqn. (2)

The answers are S1 = 12 & S2 = 4. It says solving the eqns (1) & (2)

I don't understand how the answers can be ontained by solving (1) & (2). Exactly how can the eqns be solved??

I tried squaring both the sides in Eqn. (1). But that just brings the the square term which I need to eliminate. The way I did gave me two answers for each of S1 & S2.

However, the answers are only two, not four.

Please help.